Deletion of the G protein-coupled receptor 30 impairs glucose tolerance, reduces bone growth, increases blood pressure, and eliminates estradiol-stimulated insulin release in female mice. - Mårtensson, U; Salehi, SA; Windahl, S; Gomez, M; Swärd, K; Daszkiewicz-Nilsson, J; Wendt, A; Andersson, N; Hellstrand, P; Grände, P; Owman, C; Rosen, C; et al. (2009)
In vitro studies suggest that the G protein-coupled receptor (GPR) 30 is a functional estrogen receptor. However, the physiological role of GPR30 in vivo is unknown, and it remains to be determined whether GPR30 is an estrogen receptor also in vivo. To this end, we studied the effects of disrupting the GPR30 gene in female and male mice. Female GPR30((-/-)) mice had hyperglycemia and impaired glucose tolerance, reduced body growth, increased blood pressure, and reduced serum IGF-I levels. The reduced growth correlated with a proportional decrease in skeletal development. The elevated blood pressure was associated with an increased vascular resistance manifested as an increased media to lumen ratio of the resistance arteries. The hyperglycemia and impaired glucose tolerance in vivo were associated with decreased insulin expression and release in vivo and in vitro in isolated pancreatic islets. GPR30 is expressed in islets, and GPR30 deletion abolished estradiol-stimulated insulin release both in vivo in ovariectomized adult mice and in vitro in isolated islets. Our findings show that GPR30 is important for several metabolic functions in female mice, including estradiol-stimulated insulin release.